1983
DOI: 10.1073/pnas.80.9.2656
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a family of MRNAS in a single cell type and its precursors in sea urchin embryos.

Abstract: Spec 1 mRNAs increase 100-fold in abundance per embryo during early sea urchin development. Previous studies indicated an enrichment of this mRNA in ectoderm fractions of gastrulae and plutei. We have determined the precise localization of this mRNA by in situ hybridization techniques. In pluteus larvae, the mRNA is highly restricted to a set of morphologically uniform ectoderm cells in the dorsal part of the embryo.The mRNA is not detectable in other regions of ectoderm or in endoderm and mesoderm. The patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…The latter is present at the prism stage in 300,000 copies or 750 copies per aboral ectoderm cell (32,33). This comparison suggested that SUM-1 was a rare mRNA on a per embryo basis.…”
Section: Methodsmentioning
confidence: 85%
“…The latter is present at the prism stage in 300,000 copies or 750 copies per aboral ectoderm cell (32,33). This comparison suggested that SUM-1 was a rare mRNA on a per embryo basis.…”
Section: Methodsmentioning
confidence: 85%
“…1). These cells normally express Spec1 (Lynn et al, 1983;Wikramanayake et al, 1995) (Fig. 5N,P, white arrows).…”
Section: Research Articlementioning
confidence: 99%
“…Analysis of serial sections leads us to believe that the section shown in Figure 2g passes through the border of presumptive aboral and oral ectoderm. These are regions of contiguous cells, each comprising approximately one hemisphere of differentiating ectoderm (for example, see Lynn et al 1983). The border between these regions contains cells of the presumptive ciliary band, and the unformly high labeling intensities observed here over ectoderm are consistent with this interpretation.…”
Section: Spatial Distribution Of the Spec3 Transcript During Embryogementioning
confidence: 99%
“…An impressive variety of molecular probes has been used in a number of investigations, including ones that have identified the origins and fates of several embryonic cell lineages (Lynn et al 1983;Gibson and Burke 1985;Cox et al 1986;Pehrson and Cohen 1986), studied the effects of embryonic perturbations on determination and differentation (Nemer 1986;Wessel and McClay 1987), and identified novel proteins associated with either the differentiation of embryonic cell types Wessel and McClay 1985;Leaf et al 1987) or the generation of embryonic structures (Wessel et al 1984;Benson et al 1987). …”
mentioning
confidence: 99%